Prototype Sistem Tracking Pada Aplikasi Ambulance Dan Satlantas Berbasis Protokol MQTT - Hairul Amri; Budi Sutomo (STMIK Pringsewu, 2023)
Traffic accidents often result in victims who need help quickly. Communities who know about incidents are often confused about how to take victims to health facilities quickly because there are no vehicles available to transport victims, besides that at the location of the incident there is usually a crowd of residents which causes traffic to be obstructed. This research will build a prototype accident report application that can be used by the public in reporting a traffic accident incident, POLICE and Ambulance Drivers will get information about the location of the incident that occurred to provide fast handling, and the built prototype will be measured access speed using various types of networks (GPRS, 3G, 4G), this is to see if the application can be used in various internet network conditions. The results of this study are an application that can be used to improve services for health facilities and the police, the results of the access speed test show that the built prototype can run well even though it uses a GPRS network with a speed of 1,37 seconds.